2018
DOI: 10.1007/978-3-030-01258-8_12
|View full text |Cite
|
Sign up to set email alerts
|

Sparsely Aggregated Convolutional Networks

Abstract: We explore a key architectural aspect of deep convolutional neural networks: the pattern of internal skip connections used to aggregate outputs of earlier layers for consumption by deeper layers. Such aggregation is critical to facilitate training of very deep networks in an end-to-end manner. This is a primary reason for the widespread adoption of residual networks, which aggregate outputs via cumulative summation. While subsequent works investigate alternative aggregation operations (e.g. concatenation), we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 31 publications
0
32
0
Order By: Relevance
“…Manually Designed Models Our search space contains many classic architectures designed by experts. To show the architecture discovered by our method is better than the others in the search space, we select two well-known architectures to compare with, namely U-Net [32] and SparseACN [48]. U-Net is a classic architecture that follows the encoder-decoder style.…”
Section: Resultsmentioning
confidence: 99%
“…Manually Designed Models Our search space contains many classic architectures designed by experts. To show the architecture discovered by our method is better than the others in the search space, we select two well-known architectures to compare with, namely U-Net [32] and SparseACN [48]. U-Net is a classic architecture that follows the encoder-decoder style.…”
Section: Resultsmentioning
confidence: 99%
“…A wider 101-layer residual network also achieved higher accuracy on ImageNet classification than a 200-layer network with the same model complexity [38]. One possible explanation is that residual aggregation entangles outputs from each layer and thus hinders the ability to search for new features [42]. We hence implement inlayer shortcut connections for SeqConv with concatenation instead of addition to avoid such limitation.…”
Section: Related Workmentioning
confidence: 99%
“…The extra weights assigned to earlier features give rise to a vast number of required parameters growing at an asymptotic rate of O(n 2 ), where n is the width of the SeqConv layer, whereas a regular convolutional layer merely has a linear parameter growth rate. Recent study [42] suggests that this quadratic growth suffers from significant parameter redundancy. It is observed that DenseNet, which shares the same aggregation mechanism with SeqConv, has many skip connections with average absolute weights close to zero [42,13].…”
Section: Sequentially Aggregated Transformationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the success of both ResNets and DenseNets, both aggregation types have drawbacks. For ResNets, information from the outputs of shallower layers can be lost after multiple summations with deeper layer outputs (Zhu et al 2018). This restricts feature re-usage and limits feature exploration during training.…”
Section: Introductionmentioning
confidence: 99%